2014
DOI: 10.3832/ifor1161-007
|View full text |Cite
|
Sign up to set email alerts
|

Frost damage to eucalypts in a short-rotation forestry trial in Cumbria (England)

Abstract: © iForest -Biogeosciences and Forestry IntroductionShort rotation forestry (SRF) involves growing trees in plantation at a spacing that allows rapid site capture and which are then harvested at a dbh of between 10 and 20 cm (Hardcastle 2006). The wood produced is normally used to substitute fossil fuels as a source of energy. A number of hardwoods were identified as having potential for SRF in the UK (Hardcastle 2006), but the Read Report (Read et al. 2009) highlighted the potential of eucalypts in sequestrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The native and naturalised broadleaves were able to cope with these conditions, but the eucalypts fared badly, particularly the less cold-tolerant shining gum which exhibited complete mortality over each of the two severe winters. An analysis of the cold damage at the trial is described in Leslie et al (2014). Eucalypts have been planted on a limited extent in the UK; between 2011 and 2016 nurseries sold 220,000 transplants (Purse & Leslie 2016b) and this scale represented trial rather than commercial planting.…”
Section: Discussionmentioning
confidence: 99%
“…The native and naturalised broadleaves were able to cope with these conditions, but the eucalypts fared badly, particularly the less cold-tolerant shining gum which exhibited complete mortality over each of the two severe winters. An analysis of the cold damage at the trial is described in Leslie et al (2014). Eucalypts have been planted on a limited extent in the UK; between 2011 and 2016 nurseries sold 220,000 transplants (Purse & Leslie 2016b) and this scale represented trial rather than commercial planting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, coppice rotations are more productive than first-rotations (Pukkala and Pohjonen 1990). A further approach to reduce damage is the use of intensive silviculture to accelerate establishment and growth as larger trees are more resistant to cold than smaller ones (Leslie et al 2014a). Finally, to reduce the risk of complete failure, plantations should comprise stands reflecting the full range of ages, from those recently established to those of rotation age, as younger stands are more susceptible to damage from cold.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus gunnii comes from temperate Tasmania, in contrast to E. grandis , the first sequenced Eucalyptus species (Myburg et al ), which is found in subtropical areas. E. gunnii is known as one of the most cold tolerant Eucalyptus species (Leslie et al ), but it is much less productive than E. grandis . They are therefore very representative of the apparent trade‐off between growth and stress resistance observed among the very diverse species of the genus Eucalyptus , with the most productive being the least hardy.…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore very representative of the apparent trade‐off between growth and stress resistance observed among the very diverse species of the genus Eucalyptus , with the most productive being the least hardy. Unlike most temperate trees, Eucalyptus growth is regulated by temperature rather than photoperiod (Leslie et al ), and a trade‐off between freezing resistance and growth mediated through xylem vessel anatomy has already been shown for overwintering evergreens, including Eucalyptus species (Choat et al , Maseda and Fernandez , Silva et al ). For this study, it was necessary first to identify the CBF and DREB2 genes from E. gunnii, the genome sequence of which is not publicly available.…”
Section: Introductionmentioning
confidence: 99%